Remimazolam-etomidate versus remimazolam-propofol for gastrointestinal endoscopy: A randomized controlled trial. - Baoyu Ma; Ning Zhang; Rong Huang; Shoushi Wang (PLoS ONE)
Objective The optimal sedation strategy for gastrointestinal endoscopy remains debated. This study compared the efficacy and safety of remimazolam combined with etomidate versus propofol for procedural sedation during gastrointestinal endoscopy. Methods This single-center, randomized controlled clinical trial was performed from March 2024 to April 2024. A total of 262 patients scheduled to undergo gastrointestinal endoscopy were randomly assigned to receive remimazolam-etomidate (RE) or remimazolam-propofol (RP). The primary outcome was the incidence of respiratory depression. Secondary outcomes included the results of sedation and recovery. The safety results mainly include the incidence of hypotension, bradycardia, tachycardia, painful injection and muscular tremor. Statistical analyses included t-tests, Mann-Whitney U tests, and χ² tests for group comparisons, with subgroup analyses and multivariable logistic regression to assess the robustness of primary outcome. Results Respiratory depression occurred in 20.0% (25/125) of RE patients versus 32.3% (40/124) of RP patients (OR=0.52; 95% CI = 0.29-0.93; p = 0.028). There was a statistically significant difference in the distribution of the number of airway interventions between the two groups (p = 0.043), with 18 patients (14.5%) in the RP group requiring three airway interventions and only seven patients (5.6%) in the RE group. Hypoxemia occurred in three patients (2.4%) in the RE group and in five patients (4.0%) in the RP group. Hypotension was observed in 23.2% of patients sedated with RE versus 36.3% of patients sedated with RP (p = 0.024). Conclusion Remimazolam-etomidate demonstrated a superior safety profile, with reduced respiratory depression and hemodynamic instability compared to remimazolam-propofol, suggesting its potential as a safer alternative for gastrointestinal endoscopy sedation. Registration information This trial was prospectively registered at the Chinese Clinical Trial Registry (ChiCTR2400085904) prior to patient enrollment.